Procedural protection for the disabled - عبد الله فراس عبد المنعم; يعقوب رؤى محجوب (Journal of Legal Sciences, 2019)
The increase in the number of people with special needs in general, and especially the category of the disabled, whose numbers in the communities reached about 10% - 15% (900 million disabled people in the world, on the other hand, the confirmation of constitutional texts and international conventions and domestic legislation to approve The study deals with the most important aspects of legal protection, namely, penal protection, in its procedural form. This study deals with the extent of its adequacy and its suitability to the disabled entity, which represents some of the shortcomings of its functions in contrast to its normal hypothesis. In other words, In the case of being (Jana) in the crime in view of the guarantees that a normal person is not sufficient for him and accordingly we dealt with the stages of the criminal prosecution in accordance with the determination of the adequacy of the provisions of the procedural law.